SEMANTICS OF DEATH IN G. PAHUTYAK’S COLLECTION OF ESSAYS «URIZH AND ITS SPIRITS» - Сіренко, С. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article semantics and features of the concept of death in H. Pahutyak’s collection of essays «Urizh and Its Spirits» are analyzed. The author uses a cognitive-anthropological methodology to focus on mythological background of the indicated concept, the character’s psychological reception and the construction of the semantic field of meaning.